Donabedian's structure-process-outcome quality of care model. Issue 6 (June 2015) - Moore, Lynne; Lavoie, André; Bourgeois, Gilles; Lapointe, Jean
<x xml:space="preserve">Abstract</x> BACKGROUND According to Donabedian's health care quality model, improvements in the structure of care should lead to improvements in clinical processes that should in turn improve patient outcome. This model has been widely adopted by the trauma community but has not yet been validated in a trauma system. The objective of this study was to assess the performance of an integrated trauma system in terms of structure, process, and outcome and evaluate the correlation between quality domains. METHODS Quality of care was evaluated for patients treated in a Canadian provincial trauma system (2005–2010; 57 centers, n = 63, 971) using quality indicators (QIs) developed and validated previously. Structural performance was measured by transposing on-site accreditation visit reports onto an evaluation grid according to American College of Surgeons criteria. The composite process QI was calculated as the average sum of proportions of conformity to 15 process QIs derived from literature review and expert opinion. Outcome performance was measured using risk-adjusted rates of mortality, complications, and readmission as well as hospital length of stay (LOS). Correlation was assessed with Pearson's correlation coefficients. RESULTS Statistically significant correlations were observed between structure and process QIs (r = 0.33), and process and outcome QIs (r = −0.33 for readmission, r = −0.27 for LOS). Significant positive correlations were also observed between outcome QIs (r = 0.37 for mortality-readmission; r = 0.39 for mortality-LOS and readmission-LOS; r = 0.45 for mortality-complications; r = 0.34 for readmission-complications; 0.63 for complications-LOS). CONCLUSION Significant correlations between quality domains observed in this study suggest that Donabedian's structure-process-outcome model is a valid model for evaluating trauma care. Trauma centers that perform well in terms of structure also tend to perform well in terms of clinical processes, which in turn has a favorable influence on patient outcomes. LEVEL OF EVIDENCE Prognostic study, level III.